Green Entrepreneurship in MSMEs: Marketing Challenges and Opportunities in the Context of Sustainability - Mukti Diapepin; Naufal Raid; Seven Putra; Yurismen Effendi; Yenni Jufri (PT Mattawang Mediatama Solution, 2025)
This study aims to analyze the influence of Green Marketing Strategies (GMS), Environmental Awareness (EA), and Government and Institutional Support (GIS) on Green Entrepreneurship Readiness (GER) among MSME actors in Nagari Sungai Batang, Agam Regency, West Sumatra. The research adopts a quantitative approach using Structural Equation Modeling – Partial Least Squares (SEM-PLS) analysis method. Data were collected through questionnaires from 60 MSME actors divided into three sectors: culinary, handicrafts, and agrotourism. Additionally, the Multi-Group Analysis (PLS-MGA) technique was employed to identify differences in influence across sectors. The results show that the three exogenous variables GMS, EA, and GIS simultaneously have a significant effect on GER, with an R² value of 0.62. Environmental Awareness emerges as the most influential variable. The PLS-MGA analysis revealed significant differences based on business sectors. The culinary and craft sectors show strong influences from GMS and EA, while the agrotourism sector is more affected by GIS. These findings highlight the importance of sector-specific and contextual policy approaches in empowering MSMEs through green entrepreneurship. This research contributes to the development of green entrepreneurship literature and provides an empirical basis for government and supporting institutions to design more adaptive programs in face of the challenges and opportunities of green marketing. Collaborative efforts among business actors, educational institutions, and local stakeholders are necessary to strengthen MSME readiness in facing an increasingly sustainability-oriented economic transition.